2018
DOI: 10.1021/acs.iecr.7b04963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ZnO on Characteristics and Selectivity of Coprecipitated Ni/ZnO/Al2O3Catalysts for Partial Hydrogenation of Sunflower Oil

Abstract: Ni/ZnO/Al 2 O 3 catalysts at different molar ratios were synthesized and characterized, and the catalytic performances were assessed by partial hydrogenation of sunflower oil. Ni:Zn at various molar ratios have resulted in varying degrees of Ni and Zn migration from the bulk to the catalyst surface, which led to different pore characteristics. Catalysts with equimolar Ni:Zn have shown wider pores and higher pore volumes and achieved 23% higher hydrogenation activity than Ni/Al 2 O 3 . The presence of ZnO also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…43,44 The Ni 2p 3/2 and Ni 2p 1/2 core levels were observed at 852.8 and 870.1 eV (Figure 2c 2 ), respectively, with a spin−orbital splitting of 17.3 eV, indicating that Ni ions in Ni-doped ZnO NSSs may have a valence of +2. 45 In the XPS spectra of O 1s (Figure 2a 3 , b 3 , and c 3 ), the first peak with a low binding energy around 529.6 eV can be attributed to the interaction between the O 2− ion and Zn 2+ ion in the wurtzite structure. 46 The peaks at high binding energy around 532.3 eV arose from the O−H group of H 2 O which was adsorbed on the nanoparticles surface.…”
Section: Resultsmentioning
confidence: 96%
“…43,44 The Ni 2p 3/2 and Ni 2p 1/2 core levels were observed at 852.8 and 870.1 eV (Figure 2c 2 ), respectively, with a spin−orbital splitting of 17.3 eV, indicating that Ni ions in Ni-doped ZnO NSSs may have a valence of +2. 45 In the XPS spectra of O 1s (Figure 2a 3 , b 3 , and c 3 ), the first peak with a low binding energy around 529.6 eV can be attributed to the interaction between the O 2− ion and Zn 2+ ion in the wurtzite structure. 46 The peaks at high binding energy around 532.3 eV arose from the O−H group of H 2 O which was adsorbed on the nanoparticles surface.…”
Section: Resultsmentioning
confidence: 96%
“…In this case, the enhanced removal of the chemisorbed half-hydrogenated intermediate from the active sites could prevent the further isomerisation to TFAs. This alteration in electronic properties may be used to explain the decrease in TFA formation for the sonicated catalysts, relative to the unsonicated counterpart [2] , [94] . Hence, one of the functions of ultrasound in this case of catalyst synthesis might be as a selectivity modifier for the Ni catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, one of the functions of ultrasound in this case of catalyst synthesis might be as a selectivity modifier for the Ni catalyst. Through sonication, the bonding strength of the adsorbates on the active sites were altered, which resulted in the increase of the energy barrier required for fatty acid isomerisation or the decrease of the energy barrier for hydrogenation that hastens cis -C18:1 to C18:0 conversion [94] . In particular, the shift from a higher to lower binding energy in the sonicated catalysts as observed in the XPS results ( Table 5 ) complemented this finding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak centered at about 852 eV could be corresponding to Ni 0 . The peak located at about 856 eV could correspond to nickel aluminate . The peaks at 855.8 eV, 861.5 eV were attributed to NiO. In addition, by calculating the peak area of various chemical states of Ni element in the XPS spectra, it was found that Ni 0 content increased from 12.3% to 20.2% with the increase of Nb/Ni ratio (Table S1).…”
Section: Resultsmentioning
confidence: 99%